Prevalence, awareness and control of hypertension among Tunisian adults, 2016. (30th September 2020) - Cherif, I; Ben Mansour, N; Rejaibi, S; Zoghlami, N; Saidi, O; Skhiri, A; Ben Slama, F; Ben Romthane, H; Turki, Z; Aounallah-Skhiri, H
Abstract: Background: Hypertension is becoming increasingly frequent mainly in low and middle income countries. We aimed to assess the prevalence, awareness and control of hypertension among Tunisian adults and identify associated factors with hypertension control. Methods: Data were obtained from the 2016 Tunisian Health Examination Survey, a household survey stratified at three degrees. Adults (age≥18 years old) were interviewed using an individual questionnaire, then three blood pressure measurement were performed. Participants were considered hypertensive if they were previously diagnosed or had a systolic blood pressure (SBP) ≥140mmhg and/or a diastolic blood pressure (DBP) ≥ 90mmhg during the survey. Were considered under control, treated persons with SBP<140 mmhg and a DBP<90 mmhg. A weighted binary logistic regression was used to assess associated factors with hypertension control. Input model variables were: sociodemographic variables, comorbidities and lifestyle factors. Results: In this study, 8908 adults were enrolled with a mean age of 42.8±0.2 years old and a sex ratio (M/F) equal to 0.96. Among respondents, 29.3% (95% CI: 28.2-30.5) had hypertension, 60.7% (95% CI: 58.7-62.6) of them were unaware of their disease and only (29.5%, 95% CI: 28.2-30.5) of treated patients had a controlled hypertension. In multivariate analysis, eating more than five fruits and vegetables per day was independently associated with a better hypertension control (AOR=1.7, 95% CI: 1.1-2.5). In addition, participants living in northern Tunisia were more likely to have a controlled hypertension than those living in the south (AOR=1.9, 95% CI: 1.2-2.9). Conclusions: Almost third of Tunisian adults were hypertensive. Low level of awareness and control of hypertension were found in this study. This highlights the urge to reinforce hypertension screening interventions and to strengthen educational programs on this disease with a focus on blood pressure monitoring and healthy lifestyle measures. Key messages: Tunisian adults had a low level of awareness and control of hypertension. Reinforcing hypertension screening interventions and increasing awareness about healthy lifestyle measures are recommended.